2011
DOI: 10.1111/j.1365-2966.2010.17878.x
|View full text |Cite
|
Sign up to set email alerts
|

Orbital circularization of close binary stars on the pre-main sequence

Abstract: The numerical computations of the circularization of close binary systems at the pre-mainsequence (pre-MS) stage of evolution (reported by Zahn and Bouchet in their now well-known paper) are repeated for an extended stellar mass interval of M = 0.1-2.7 M , based on modern evolutionary pre-MS stellar models and on the modified Zahn theory. The new results mostly corroborate those obtained by Zahn and Bouchet in the mass interval M = 0.5-1.25 M covered by their work. To compare the theoretically expected results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 90 publications
(98 reference statements)
1
12
0
1
Order By: Relevance
“…The coupled stellar-tidal orbital evolution of binary systems has been extensively studied in the literature for systems ranging from star-star binaries (e.g. Huang 1966;Mestel 1968;van't Veer & Maceroni 1988;Zahn & Bouchet 1989;Li & Wickramasinghe 1998;Khaliullin & Khaliullina 2011) to star-planet binaries (e.g. Dobbs-Dixon et al 2004;Barker & Ogilvie 2009;Lanza & Mathis 2016) to even star-compact object binaries (e.g.…”
Section: Coupled Stellar-tidal Evolutionmentioning
confidence: 99%
“…The coupled stellar-tidal orbital evolution of binary systems has been extensively studied in the literature for systems ranging from star-star binaries (e.g. Huang 1966;Mestel 1968;van't Veer & Maceroni 1988;Zahn & Bouchet 1989;Li & Wickramasinghe 1998;Khaliullin & Khaliullina 2011) to star-planet binaries (e.g. Dobbs-Dixon et al 2004;Barker & Ogilvie 2009;Lanza & Mathis 2016) to even star-compact object binaries (e.g.…”
Section: Coupled Stellar-tidal Evolutionmentioning
confidence: 99%
“…As the eclipsing components are being driven by tides toward synchronization to their orbital motion, radial contraction is changing the spin rates via conservation of angular momentum. In addition, Zahn & Bouchet (1989) and Khaliullin & Khaliullina (2011) both argue that the orbital period of Par 1802 is small enough for circularization and synchronization to occur prior to the arrival on the main sequence. As such, the assignment of P 1 as the rotational period of both eclipsing components is reasonable.…”
Section: Notesmentioning
confidence: 99%
“…Radial contraction will also enter into the angular momentum evolution through the rotational frequency (Equations (B3) and (B12)). Thus, we have added radial contraction to the CPL and CTL models, in a manner similar to that in Khaliullin & Khaliullina (2011), but note that their treatment does not include obliquity effects. D 'Antona & Mazzitelli (1997) and Baraffe et al (1998) provide from their calculations the time rate of change of the radius, dR/dt in R /Myr, for 0.4 M stars.…”
Section: Tidal Evolution and Heatingmentioning
confidence: 99%
“…As the radius enters the tidal evolution at the 5 th power, the radial contraction is a major effect. Khaliullin and Khaliullina (2011) revisited this point and found that, although radial contraction does play a major role, they were unable to combine models of the equilibrium tide and radial contraction to match observations. Weinberg et al (2011) tested the linear theory against nonlinear models and found that in general the linear theory does not capture the physics of the more sophisticated approach.…”
Section: E4 Tidal Response In Celestial Bodiesmentioning
confidence: 99%